2010
DOI: 10.5551/jat.3616
|View full text |Cite
|
Sign up to set email alerts
|

Brachial-ankle Pulse Wave Velocity as an Index of Central Arterial Stiffness

Abstract: Aim: Stiffness of the central arteries plays an important role in the pathophysiology of cardiovascular disease, and pulse wave velocity (PWV) of the aorta has been used as the standard measure of central arterial stiffness. An automated device for brachial-ankle (ba) PWV is available, although information is limited whether baPWV reflects the stiffness of central or peripheral arteries. We therefore addressed this question in the present study. Methods: The subjects were 2,806 consecutive participants in our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
116
2
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(127 citation statements)
references
References 31 publications
6
116
2
3
Order By: Relevance
“…It has been reported that baPWV is an index of arterial stiffness with similar characteristics to aortic PWV 26) , and is a marker of severity of atherosclerotic vascular damage as well as a predictor of prognosis in patients with cardiovascular disease 27) ; however, PWV is strongly influenced by blood pressure and age 9) . Blood pressures were unchanged throughout the study, and there was no difference in the amount of change in baPWV between the two groups, although the increase in the median baPWV value from baseline was greater in the statin-only group than in the combined-therapy group.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that baPWV is an index of arterial stiffness with similar characteristics to aortic PWV 26) , and is a marker of severity of atherosclerotic vascular damage as well as a predictor of prognosis in patients with cardiovascular disease 27) ; however, PWV is strongly influenced by blood pressure and age 9) . Blood pressures were unchanged throughout the study, and there was no difference in the amount of change in baPWV between the two groups, although the increase in the median baPWV value from baseline was greater in the statin-only group than in the combined-therapy group.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with CKD, aortic pulse wave velocity showed a significant increase in placebo-treated patients but not in statin-treated patients 29) . Since aortic pulse wave velocity is an index of arterial stiffness showing similar characteristics to those of brachial-ankle pulse wave velocity, the cholesterol-lowering agents used in this study could also have potential to improve arterial stiffness 30) . One possible explanation for the absence of an improvement in arterial stiffness despite the improvement in eGFR is that this study did not have sufficient statistical power to allow reliable estimation of the effects of add-on ezetimibe on surrogate markers for arterial stiffness.…”
Section: Efficacy Of Add-on Ezetimibe On Arterial Stiffnessmentioning
confidence: 99%
“…Brachial-ankle PWV (BaPWV) has been shown to be an index of central arterial stiffness with a good correlation with the aortic PWV obtained by invasive recording, which has been demonstrated to have a close relationship with carotid-femoral PWV 9,11) . Previous studies have also shown that baPWV is strongly associated with cardiovascular diseases and metabolic syndrome 4,12,13) .…”
Section: Introductionmentioning
confidence: 99%